2021
DOI: 10.1038/s41524-021-00574-w
|View full text |Cite|
|
Sign up to set email alerts
|

Graph neural networks for an accurate and interpretable prediction of the properties of polycrystalline materials

Abstract: Various machine learning models have been used to predict the properties of polycrystalline materials, but none of them directly consider the physical interactions among neighboring grains despite such microscopic interactions critically determining macroscopic material properties. Here, we develop a graph neural network (GNN) model for obtaining an embedding of polycrystalline microstructure which incorporates not only the physical features of individual grains but also their interactions. The embedding is th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(50 citation statements)
references
References 38 publications
0
50
0
Order By: Relevance
“…Thus, developing ML models with both high predictive ability and high interpretability has been the hot pursuit of materials scientists. [87,113,[204][205][206][207] Recently, physics-informed ML integrates data and mathematical models, which may provide a new insight to discover hidden physics and tackle high-dimensional problems. [50] Altogether, keeping the balance of quantifiable interpretability and intelligent forecasting of ML is a daunting challenge that requires deep integration and collaboration across multiple disciplines.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, developing ML models with both high predictive ability and high interpretability has been the hot pursuit of materials scientists. [87,113,[204][205][206][207] Recently, physics-informed ML integrates data and mathematical models, which may provide a new insight to discover hidden physics and tackle high-dimensional problems. [50] Altogether, keeping the balance of quantifiable interpretability and intelligent forecasting of ML is a daunting challenge that requires deep integration and collaboration across multiple disciplines.…”
Section: Discussionmentioning
confidence: 99%
“…In [77], the authors applied layerwise-relevance propagation to characterize the relevant nodes and features for a MLPF model while in [151] the authors apply symbolic regression as a form of disentangled representation learning to extract explicit physical relations including known force laws and Hamiltonians and a new analytic formula that can predict the concentration of dark matter from the mass distribution of nearby cosmic structures. There are also a few examples from the broader physical sciences space; in [152] the authors use an Integrated Gradient method for sensitivity analysis to characterize the relationship between individual material grains and overall material property prediction and in [153] the authors apply a counterfactual perturbation method to understand which components of molecules make them active for disease treatment.…”
Section: Interpretability and Explainabilitymentioning
confidence: 99%
“…for molecular design) by quantifying the strength of the contributions of the atom and atom-pair features towards the material property. 145,146 Besides interpreting trained ML models to discover underlying physical laws governing a material property, machine learning techniques can also be used to train accurate yet simple predictive models that are easy to interpret. For example, a recent study 147 reported training neural networks with adjustable parameters quantifying the complexity of the learned functions to find accurate and physically interpretable expressions for predicting a material property of interest.…”
Section: Interpretability Of Modelsmentioning
confidence: 99%